Analysis of Answering Process on Problem Solving Ability Through Problem-Based Learning Model: Analisis Proses Jawaban Kemampuan Pemecahan Masalah Melalui Model Problem-Based Learning - Sari, Nilam; Saragih, Sahat; Napitupulu, E Elvis; Rakiyah, Siti; Suciawati, Hasni; Anim, Anim (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
This study was made to find out how the process of completing student answers incompleting the problem-solving ability test through a problem-based learning model.The process of completing the answers to the mathematical problem solving ability test can be viewed from 2 (two) aspects, namely:1) the procedure used in solving the problem and, 2)the mistakes made by students in answering the questions/the problems.The population of this study were all third semester students majoring in informatics management at all STMIK in Medan and samples were taken at random and two STMIKs were selected with accreditations B and C. The type of this research was a qualitative descriptive analysis with the instrument was the test of problem solving abilities. This study gave the result that the problem solving process carried out by students through problem-based learning was better than conventional learning, the firs result is the number of students doing the test who obtained a "good" assessment category in the experimental class was more than the control class (Nexperiment = 67 > Ncontrol = 17 ). The second result is the test given as a whole it could be done well by students in accordance with the existing questions/problems, although some still forgot to check the answers. In addition, at every meeting there were group members who werenot active in discussing. They always busy with other things, it caused friends in one group to be disturbed.The results of this study can be used as a reference for teachers who want to implement problem-based learning.